PENANAMAN NILAI PANCASILA MELALUI PEMBELAJARAN PPKN BERBASIS KEARIFAN LOKAL - Yusril Maidah, Sri; Jamilah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The cultivation of Pancasila values in the era of globalization faces significant challenges, including moral shifts and the fading of national identity among the younger generation. This study aims to explore the effectiveness of integrating local wisdom into Pancasila and Civic Education (PPKN) as a means of internalizing the nation's ideological values. Using a literature review method analyzing academic sources published between 2021 and 2025, this research examines various contextual approaches that bridge regional traditions with the principles of Pancasila. The findings indicate that local wisdom—encompassing customary laws, oral traditions, and local philosophies—functions as a living laboratory that renders civic education materials more relevant and accessible to students. This integration is proven to enhance the affective domain of learners, particularly in strengthening attitudes of tolerance, mutual cooperation (gotong royong), and patriotism. Furthermore, the use of culture-based learning media and digital technology to document regional values provides an innovative dimension to character education. The study concludes that the synergy between national curriculum standards and regional socio-cultural richness is crucial for developing citizens who are deeply rooted in their cultural identity yet remain open-minded.